Bardet Biedl Syndrome: A Case Report (BIRDEM Medical Journal, 2019)
Bardet Biedl syndrome is a rare heterogenous autosomal recessive disorder. A very few cases were reported in Bangladesh. A 12-year-old boy presented with childhood obesity, polydactyly in all 4 limbs, bilateral gynaecomastia, acanthosisnigricans, night blindness and mental retardation. After hormonal evaluation he was found to have hypogonadotrophichypogonadism, dislipidaemia, renal impairment, elevated liver enzymes and retinitis pigmentosa. We advised him to reduce weight and implemented and weight reducing diet. Levothyroxine and metformin were started. He was scheduled for eye check-up every 3 months and follow up at endocrinology.Birdem Med J 2019; 9(2): 162-164